Pulmonary Sequestration and Diaphragmatic Eventration in a 6-month-old Infant - Hsing-Ching Kuo; Chich-Yang Chang; Joseph-Hang Leung (Pediatrics and Neonatology)
A congenital pulmonary malformation, such as pulmonary sequestration or congenital cystic adenomatoid malformation, should be suspected in infants with recurrent lower respiratory symptoms or unifocal infiltrations. The possibility of congenital pulmonary malformation associated with additional abnormalities, such as diaphragmatic hernia, is relatively high and can lead to misdiagnosis. We report a case of a 6-month-old girl who presented with relapsing respiratory infection and hematemesis. Computerized axial tomography scan and barium swallowing study were performed, revealing a suspected intralobar pulmonary sequestration associated with sliding gastric hernia. Since the patient’s condition was complicated by sliding hernia, pneumonia and pleural effusion, a surgical procedure instead of cardiac catheterization with coil embolization was performed. During surgery, the absence of a sliding gastric hernia but a diaphragmatic eventration was noted. Only a partial portion of the left-side diaphragm was relaxing, making the barium swallowing study difficult to interpret. This case serves as a reminder that if pulmonary sequestration is suspected, a full work-up with a complete set of imaging studies should be ordered for the possible detection of associated gastrointestinal, respiratory and thoracic abnormalities.